Break-Even Analysis under Two Cost Scenarios for Profit Planning: Evidence from Donat Zahira MSME in Rengasdengklok - Deya Cesika; Dara Dwi Apriliani; Anisa Pratiwi; Endin Yulia Risqi Saputri; Nadya A Siahaan; Suci Hupalia; Yuni Prasojo Putri (Riset Anak Bangsa, 2026)
Donat Zahira, a microenterprise in Rengasdengklok, has not systematically applied break-even point (BEP) analysis to determine its minimum sales threshold and profit targets, despite fluctuations in raw material costs. This study analyzes the application of BEP analysis as a basis for profit planning. A descriptive case-study design was employed. Data were collected through observation, an interview with the owner, and records of costs and production volume over four weeks. The data were analyzed using a cost-volume-profit approach. Profit amounted to IDR 2,125,000 in Weeks 1 and 3 and IDR 2,325,000 in Weeks 2 and 4. The weighted-average variable cost was IDR 1,449.04 per unit. Under the average-cost scenario, the break-even point was 1,023 units, equivalent to sales of IDR 2,557,197. Under the conservative scenario, it was 1,075 units, equivalent to IDR 2,687,500. An average weekly profit target of IDR 2,225,000 required sales of approximately 3,140 units, or IDR 7,850,000. The enterprise operated above the break-even threshold; however, regular cost recording and periodic sales-target updates are required to support more systematic decisions.